Crude palm oil market volatility: pre and post crisis periods. Evidence from Qarch - Haron, Razali; Salami, Mansurat Ayojimi (2015)
This study aims to examine the volatility of Malaysian Crude Palm Oil (CPO) markets for it has important implication to both business communities and policy makers. This study adopted the GARCH (1,1) model and the result of the finding exhibited persistent volatility as well as volatility clustering in Malaysian CPO market. The persistent volatility implies that the percentage of market volatility is closer to unity. This reflects the frequency of occurrence of the CPO markets volatility while volatility clustering provides useful information on the broadness of the shock. Adequate understanding on the degree of volatility of the market can instigate informed decision by policy makers which may mitigate persistent uncertainty of returns. Business communities will consistently be alert on market volatility and ready to make sound decision on any events of the market. This study enhances the understanding on commodity market volatility by quantifying the half-life of decay of the shock in the market and contributes to the literature by providing in sight information on the volatility of the market.